Barrier analysis for daily fruit and vegetable consumption among low income consumers in Ibadan, Nigeria - Samuel, Folake; Adeyemi, Olutayo A.; Meldrum, Gennifer; Kennedy, Gina; Shittu, Oluyemisi O. (Bioversity International, 2020)
Barrier analysis is completed with at least 45 doers of the behavior of interest and 45 non-doers who do not practice the behaviour. In this case, the behaviour of interest was the consumption of an adequate quantity and diversity of fruits and vegetables by low income adults in the focal neighbourhoods. Doers and non-doers were identified based on multi-pass quantitative 24-hour dietary recall surveys that were completed with a subset of households, targeting an adult man and adult woman, with at least two days between the recalls. 241 women and 131 men completed the dietary recall surveys. The results were reviewed to identify respondents with higher and lower fruit and vegetable intakes. Doers consumed fruit in at least one of the two recall periods and always consumed at least one type of vegetable. Non-doers did not consume fruit in any of the recall periods. Lists of non-doers and doers were compiled according to gender and neighbourhood and sorted in a random order to interview following a quota sampling approach. Enumerators visited each household to request their participation in the survey.